2002
DOI: 10.1021/ma012170h
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of CF2-Modified Polybutadiene and Polyisoprene in Supercritical Carbon Dioxide

Abstract: The cloud-point behavior of fluorinated polyisoprenes (FPI) and fluorinated polybutadienes (FPBD) in supercritical fluid (SCF) CO2 are reported at temperatures from 60 to 170 °C and pressures from 1000 to 3000 bar. These fluorinated polymers were prepared by the addition of difluorocarbene (CF2) to the parent polydienes yielding a gem-difluorocyclopropane repeating unit, a segment containing both fluorine and a significant dipole moment. Neither the unmodified polyisoprene starting material nor the hydrogenate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 20 publications
(44 reference statements)
3
32
0
Order By: Relevance
“…In addition, the CF 3 groups are expected to create local dipole moments in this part of the repeat group. It should also be noted 9 showed that incorporating difluorocarbene (CF 2 ) into a polybutadiene or polyisoprene repeat group yields a gemdifluorocyclopropane repeat group that contains fluorine and has a significant dipole moment. Both the fluorinated isoprene and the butadiene polymers dissolve in CO 2 , but pressures in excess of 1000 bar are needed to obtain a single phase.…”
mentioning
confidence: 99%
“…In addition, the CF 3 groups are expected to create local dipole moments in this part of the repeat group. It should also be noted 9 showed that incorporating difluorocarbene (CF 2 ) into a polybutadiene or polyisoprene repeat group yields a gemdifluorocyclopropane repeat group that contains fluorine and has a significant dipole moment. Both the fluorinated isoprene and the butadiene polymers dissolve in CO 2 , but pressures in excess of 1000 bar are needed to obtain a single phase.…”
mentioning
confidence: 99%
“…We propose that the increased stiffness-the resistance of the resulting elastic structure to deflection by an applied force-is due to the presence of fluorine in the CF 3 −(CH 2 ) 2 −[Si−O−] n chains, which is well known to promote orientation by lateral interactions [9]. Too high a level of fluorination, such as in the case of the perfluorinated samples, produces an adverse effect, due to the dominance of interactions within the polymer chains [10]. On the other hand, the influence of the degree of the sol-gel reactions at the moment of spinning is clear comparing films prepared at low spin velocity from sols with the same precursor but with different hydrolysis conditions (TFP3 and TFA3).…”
Section: Resultsmentioning
confidence: 99%
“…As exemplified several times in the previous sections, many compoundswhether they be substrates or catalysts-show increased affinity to CO 2 if they are modified by fluorination [167][168][169]. Therefore, the addition of fluorinated pony tails to existing chemical structures or ligand frameworks as exemplified in Sect.…”
Section: Interactions Of Carbon Dioxide With Fluorinated Compoundsmentioning
confidence: 88%